Dyslipidemia management among patients with high and very high cardiovascular risk in Indonesia: a multi-center registry - Sunanto Ng; Anwar Santoso; Renan Sukmawan; Erwinanto Erwinanto; Erika Adam; Dwita Desandri; Rita Zahara; Sony Wicaksono; Magma Purnawan Putra; Teuku Heriansyah; Badai Bhatara Tiksnadi; Yusra Pintaningrum (The Indonesian Heart Association, 2026)
In “Dyslipidemia management among patients with high and very high cardiovascular risk in Indonesia: a multi-center registry” (Indonesian Journal of Cardiology, 46(2), 51-63. https://doi.org/10.30701/ijc.1880), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1880. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1880